How the InfraGuardTM Intelligent Slope and Embankment Monitoring System increases safety in railroads - Peter Berger; Michał Dąbrowski (Przegląd Komunikacyjny)
Abstract: A typical solution for the construction of transportation infrastructure around the world is the economic adjustment of their course to the natural terrain. Hence, road and railway construction on embankments or in indentations is typical. Recent climate change is triggering extreme conditions and weather events that have a significant impact on the stability of slopes. Such disturbances may manifest themselves in gradual long-term subsidence, or in sudden, unforeseen landslides and collapses, and constitute a serious threat to human life. Keywords: Monitoring system; Slope; Embankment; Safety in railway issues